La sexualité de M. Homais - Shoshana-Rose Marzel (Flaubert: Revue Critique et Génétique)
According to many researchers, by making Homais the mythical incarnation of the nineteenth century Bourgeois, Flaubert automatically reduces Homais' sexual activity. Being married with children, the pharmacist's sexuality (in its traditional sense) would be almost non-existent, only turned to the reproduction of the species. Another interpretation is being proposed here: not only does Homais enjoy a fulfilling sexual life (with his wife), but it is done according to Homais' progressive and Voltarian philosophy. Through Homais, Flaubert exposes (perhaps with anxiety and despair) the Bourgeois happy sexuality, as the expression of the triumph of his materialist philosophy, in the face of the collapse of Romanticism.